Raman Spectroscopy Characterization of Dissolved Polysilicon Byproduct SiCl4 in Ionic Liquids - Cheng Cheng; Chenglong Zhang; Jiachao Jiang; En Ma; Jianfeng Bai; Jingwei Wang (Journal of Spectroscopy)
Silicon tetrachloride (SiCl4) is the main byproducts of the polysilicon industries. The dissolution behaviors of SiCl4 in imidazolium ionic liquid, including [Bmim]OTf, [Bmim]NTf2, [Hmim]NTf2, and [Omim]NTf2, were investigated for recycling Si from SiCl4. Raman spectroscopy was used to understand the combination between the ionic liquid and SiCl4, and the conductivity of ionic liquids in different conditions was determined. The results indicated that [Bmim]NTf2 exhibited a better SiCl4 dissolving capacity compared to [Bmim]OTf, longer alkyl chain lengths in the imidazolium cations of the ionic liquids exhibited a better performance in dissolving SiCl4, and [Bmim]NTf2 : PC = 1 : 2 exhibited the best conductivity. In addition, molecular bondings between C-Cl, Si-O-Si, and C-Si were formed between the ionic liquids and SiCl4.